Scratch-resistant and wear-resistant aerial cable and production process thereof

By modifying boron nitride and polyurethane resin, a sheath layer with high hydrolysis resistance and heat resistance is prepared, which solves the aging problem of polyurethane materials under high humidity and high temperature conditions, and improves the wear resistance and use of cables. Security.

CN119307086AInactive Publication Date: 2025-01-14ZHONGSHENG HONGTONG ELECTRIC POWER TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411428252.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyurethane materials are easily hydrolyzed under high humidity and high temperature conditions, resulting in aging and reducing strength of materials. Antioxidants are prone to failure in polymer matrix, which cannot effectively avoid the aging and degradation of materials, and boron nitride cannot be evenly dispersed in polymer matrix and The formation of effective interface combination limits its enhancement effect.

Method used

Hydroxylated boron nitride is used as a thermal filler, and modified by phenothiazine structure and polysilicon oxygen chain to form an alkenyl group and epoxy product on the surface, enhance the compatibility and dispersion of boron nitride, and combine with polyurethane resin, Flame retardant and anti-hydrolyzer, a sheath layer material with excellent wear resistance is prepared.

Benefits of technology

It significantly improves the heat dissipation, mechanical properties and aging resistance of the cable, extends the cable life, avoids oxidative aging and degradation, and improves hydrolysis resistance and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082811090000151
    Figure BDA0005082811090000151
Patent Text Reader

Abstract

The invention discloses a scratch-resistant and wear-resistant aerial cable and a production process thereof, and relates to the field of aerial cables, the scratch-resistant and wear-resistant aerial cable comprises a conductor, an insulating layer and a sheath layer from inside to outside, and the sheath layer comprises the following raw materials in parts by weight: 60-80 parts of polyurethane resin, 15-25 parts of a heat-conducting filler, 10-15 parts of a flame retardant, 0.8-1.0 part of an ultraviolet light absorber and 1-1.5 parts of an anti-hydrolysis agent. The polyurethane-based cable sheath material has excellent wear resistance, and meets the use requirements of scratch resistance and wear resistance of overhead cables. The synthesized heat-conducting filler comprises boron nitride, a phenothiazine structure, secondary hydroxyl and the like, so that the heat dissipation performance, the mechanical property and the aging resistance of the cable are improved. The synthesized anti-hydrolysis agent comprises a polyurethane structure, a polymeric carbodiimide structure and a polysiloxane chain, so that the hydrolysis resistance and heat resistance of the cable are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of overhead cables, and in particular to a scratch-resistant and wear-resistant overhead cable and a production process thereof. Background Art

[0002] Overhead cables are overhead wires equipped with an insulating layer and a protective sheath. They are a new high-voltage power transmission method between overhead wires and underground cables. They have the main characteristics of high power supply reliability, good power supply safety, convenient installation and maintenance, and reasonable economy. Cable sheath materials include polyvinyl chloride (PVC), polyethylene (PE), polyurethane (PUR), thermoplastic elastomer (TPE / TPR), nylon (PA), fluoroplastics, silicone rubber, chloroprene rubber, chlorosulfonated polyethylene, low-smoke halogen-free polyolefin, polytetrafluoroethylene (PTFE), etc. Among them, polyurethane-based cable sheath materials are widely used due to their high wear resistance, low temperature resistance, oil resistance and other advantages.

[0003] However, the ester group of polyurethane materials is easily hydrolyzed under conditions of high humidity and high temperature, resulting in material aging and reduced strength, which limits the use of sheath materials in rainy and humid environments. When the temperature rises, the strength and oil resistance of the polyurethane sheath material will decrease. Therefore, a suitable modification method is needed to improve the hydrolysis resistance and heat resistance of the polyurethane sheath material.

[0004] During long-term use, polyurethane materials are inevitably affected by light, heat, oxygen, etc. and age and degrade. Antioxidants are usually added, but small molecule antioxidants are easy to migrate and fail in the polymer matrix, thus losing their anti-oxidative aging effect and failing to effectively prevent the aging and degradation of the material. Boron nitride is a crystal composed of nitrogen atoms and boron atoms. It has high thermal conductivity, good insulation, high temperature and chemical stability, etc. It has significant advantages in the application of cable sheath materials. However, due to the inertness of the surface of boron nitride and the lack of active groups, it cannot be evenly dispersed in the polymer matrix and cannot form an effective interface bond, which greatly limits its reinforcing effect on the polymer matrix. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a scratch-resistant and wear-resistant overhead cable and a production process thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A scratch-resistant and wear-resistant overhead cable, comprising a conductor, an insulating layer and a sheath layer from the inside to the outside; the conductor is formed by twisting a number of hard copper wires, and the insulating layer is made of a cross-linked polyethylene insulating material;

[0008] The sheath layer comprises the following raw materials by weight: 60-80 parts of polyurethane resin, 15-25 parts of thermal conductive filler, 10-15 parts of flame retardant, 0.8-1.0 parts of ultraviolet absorber, and 1-1.5 parts of anti-hydrolysis agent; the flame retardant is DOPO, and the ultraviolet absorber is UV-329;

[0009] The preparation of the scratch-resistant and wear-resistant overhead cable comprises the following steps:

[0010] Step S1: placing the polyurethane resin in a drying oven at 105° C. for 7-8 hours to obtain a dried polyurethane resin, placing the thermal conductive filler, flame retardant, ultraviolet absorber, and anti-hydrolysis agent in an infrared dryer for 35-45 minutes, adding them together with the dried polyurethane resin to a mixer, stirring and mixing at a speed of 200-300 r / min for 10-15 minutes to obtain a mixture, and melt-extruding and granulating the mixture in a twin-screw extruder to obtain a sheath layer material;

[0011] Step S2: twisting a number of hard copper wires to form a conductor; extruding a cross-linked polyethylene insulation material on the outer periphery of the conductor to form an insulation layer; and finally extruding the sheath layer material on the outer periphery of the insulation layer to form a sheath layer, thereby obtaining a scratch-resistant and wear-resistant overhead cable.

[0012] The preparation of the thermally conductive filler comprises the following steps:

[0013] Step A1: Mix potassium hydroxide and sodium hydroxide and grind them for 35-45 minutes, then place them in a high-pressure reactor, add hexagonal boron nitride, heat and react at 180° C. for 2 hours, and obtain hydroxylated boron nitride by filtering and centrifuging;

[0014] Furthermore, the usage ratio of potassium hydroxide, sodium hydroxide and hexagonal boron nitride is 48.5 mol:51.5 mol:10-15 g;

[0015] During the reaction of step A1, under the action of molten potassium hydroxide and sodium hydroxide, the edges of the hexagonal boron nitride sheets will curl themselves up, and at the same time, ions such as OH - It will intercalate into the curled hexagonal boron nitride sheets, so that the hexagonal boron nitride nanosheets are gradually peeled off from the bulk hexagonal boron nitride, and at the same time, the hydroxylation modification of the hexagonal boron nitride surface is achieved to obtain hydroxylated boron nitride;

[0016] Step A2: Add hydroxylated boron nitride to toluene, ultrasonically disperse for 40 minutes, add linoleic acid and N, N'-dicyclohexyl diimide under stirring, heat to 110-120°C, reflux with constant temperature stirring for 48-51 hours, then centrifuge for 10-15 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain boron nitride containing alkenyl groups on the surface;

[0017] Further, the usage ratio of hydroxylated boron nitride, toluene, linoleic acid and N,N'-dicyclohexyldiimide is 5-7 g:120 mL:10 g:2 g;

[0018] During the reaction of step A2, the hydroxyl groups on the surface of the hydroxylated boron nitride react with linoleic acid to generate boron nitride containing alkenyl groups on the surface;

[0019] Step A3: Add the boron nitride containing alkenyl groups on the surface into dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4-5 hours to obtain an epoxy product;

[0020] Furthermore, the amount ratio of the boron nitride containing alkenyl groups on the surface, dichloromethane and 3-chloroperoxybenzoic acid is 12-16 g: 80-90 mL: 0.1 mol;

[0021] During the reaction of step A3, the alkenyl groups in the surface of the boron nitride containing alkenyl groups are oxidized to epoxy groups to obtain an epoxy product;

[0022] Step A4: Add 2-cyanophenothiazine to tetrahydrofuran, start stirring, add Raney nickel and Pd / C, introduce hydrogen, and react under normal pressure for 48 hours to obtain a primary amino product; add the primary amino product and the epoxy product to a flask, add dimethyl sulfoxide, stir and react at 60° C. for 24 hours, filter and dry to obtain a thermal conductive filler;

[0023] Further, the dosage ratio of 2-cyanophenothiazine, tetrahydrofuran, Raney nickel and Pd / C is 0.1 mol:100-110 mL:0.02 mol:0.05-0.06 mol; the dosage ratio of primary amino product, epoxy product and dimethyl sulfoxide is 46-50 g:14-18 g:150 mL;

[0024] During the reaction of step A4, the cyano group of 2-cyanophenothiazine is reduced to an amino group to obtain a primary amino product; the epoxy group of the epoxy product reacts with the primary amino group in the primary amino product to obtain a thermally conductive filler;

[0025] The preparation of the anti-hydrolysis agent comprises the following steps:

[0026] Step B1: Add 4-nitrostyrene to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, and stir at room temperature for 4-5 hours to obtain the epoxy product 1;

[0027] Further, the dosage ratio of 4-nitrostyrene, dichloromethane and 3-chloroperoxybenzoic acid is 0.1 mol:50-60 mL:0.1 mol;

[0028] During the reaction of step B1, the olefin group in 4-nitrostyrene is oxidized to an epoxy group to obtain an epoxy product 1;

[0029] Step B2: In a nitrogen atmosphere, add 1,3-bis(3-carboxypropyl)tetramethyldisiloxane and toluene into a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product 1 into the flask, stir and react for 8-10h, then heat to 110-120°C, stir for 1-2h to obtain the nitro product;

[0030] Further, the usage ratio of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane, toluene, pyridine and epoxy product 1 is 0.1 mol:180-190 mL:0.020-0.025 mol:0.2 mol;

[0031] During the reaction of step B2, the carboxyl group of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane undergoes a ring-opening reaction with the epoxy group of the epoxy product 1 to obtain a hydroxyl-containing nitro product;

[0032] Step B3: After mixing the nitro product and hexyl isocyanate, add a 20% by mass dilute sulfuric acid solution and methanol, and react at 50° C. for 4 hours to obtain a nitro product containing carbamate; add the nitro product containing carbamate and ethyl acetate into a three-necked flask, heat to 45-55° C., start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5 hours to obtain a dibasic aromatic primary amine;

[0033] Furthermore, the dosage ratio of the nitro product, hexyl isocyanate, 20% dilute sulfuric acid solution and methanol is 1 mol: 2 mol: 100 mL: 200 mL; the dosage ratio of the nitro product containing carbamate, ethyl acetate and sodium dithionite is 0.1 mol: 240-250 mL: 0.2-0.25 mol;

[0034] During the reaction of step B3, the hydroxyl group in the nitro product reacts with the isocyanate group of hexyl isocyanate to generate a nitro product containing carbamate; the nitro group in the nitro product containing carbamate is reduced to an amino group to obtain a dibasic aromatic primary amine;

[0035] Step B4: Add xylene to a four-necked flask, introduce nitrogen, add dibasic aromatic primary amine and triphosgene at 75°C, respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain dibasic isocyanate; add dibasic isocyanate to a flask, then add 3-methyl-1-phenyl-2-phosphopentene-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent;

[0036] Furthermore, the dosage ratio of xylene, dibasic aromatic primary amine and triphosgene is 260 mL: 0.1 mol: 0.2 mol; the dosage ratio of dibasic isocyanate and 3-methyl-1-phenyl-2-phosphopentene-1-oxide is 0.1 mol: 0.0030-0.0035 mol;

[0037] During the reaction of step B4, the amino group of the dibasic aromatic primary amine reacts with triphosgene to generate chloroamide, which is then heated to dehydrochlorinate to generate dibasic isocyanate; the dibasic isocyanate is catalytically decarbonated to generate an anti-hydrolysis agent.

[0038] Beneficial effects of the invention: The invention discloses a scratch-resistant and wear-resistant overhead cable, which includes a conductor, an insulating layer and a sheath layer from the inside to the outside, and the sheath layer is prepared from raw materials such as polyurethane resin, thermal conductive filler, flame retardant, ultraviolet absorber and anti-hydrolysis agent. The polyurethane-based cable sheath material has excellent wear resistance and meets the use requirements of the scratch-resistant and wear-resistant performance of the overhead cable.

[0039] The synthesized thermal conductive filler includes boron nitride, phenothiazine structure and secondary hydroxyl group. After the hexagonal boron nitride is modified by hydroxylation and subsequent reaction, the compatibility and dispersibility of boron nitride in polyurethane are increased, and the secondary hydroxyl group participates in the hydrogen bond cross-linking network of the polyurethane system, further enhancing the dispersion of the thermal conductive filler in the matrix, so that the boron nitride can better play the role of improving the heat dissipation and mechanical properties of the sheath layer material, and can effectively conduct away the heat generated during the operation of the cable to avoid overheating, thereby improving the safety of the cable and extending the life of the cable; the phenothiazine structure has the role of peroxide free radical terminator and peroxide decomposer in the oxidative degradation reaction of the polymer, and its grafting into boron nitride can avoid the failure of small molecule migration, and at the same time, it is dispersed as the thermal conductive filler is dispersed in the matrix, which is more conducive to inhibiting the oxidative aging degradation of the sheath layer material; therefore, adding the thermal conductive filler can improve the heat dissipation, mechanical properties and aging resistance of the cable.

[0040] The synthesized anti-hydrolysis agent molecules include polyurethane structure, polymeric carbodiimide structure and polysiloxane chain; the polyurethane structure is similar to the polyurethane molecular chain structure, so that the compatibility and dispersion of the anti-hydrolysis agent in the matrix are better; the polymeric carbodiimide has a higher relative molecular mass and has the advantages of higher thermal stability and low dosage and high effect compared with monomeric carbodiimide, so that the anti-hydrolysis agent can play a role stably, improve the hydrolysis resistance of the sheath layer material, and avoid the degradation of the cable sheath performance due to the hydrolysis reaction of polyurethane; the SiO-Si bond and SiC bond contained in the polysiloxane chain have higher bond energy and high energy required for breaking, so that the thermal stability of the sheath layer material is improved, thereby improving the heat resistance of the cable; the anti-hydrolysis agent is added to improve the hydrolysis resistance and heat resistance of the cable. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] A thermally conductive filler, the preparation of which comprises the following steps:

[0044] Step A1: Mix potassium hydroxide and sodium hydroxide and grind them for 35 minutes, then place them in a high-pressure reactor, add hexagonal boron nitride, heat and react at 180°C for 2 hours, and obtain hydroxylated boron nitride by filtering and centrifugation; the dosage ratio of potassium hydroxide, sodium hydroxide and hexagonal boron nitride is 48.5 mol:51.5 mol:10 g;

[0045] Step A2: Add hydroxylated boron nitride to toluene, ultrasonically disperse for 40 minutes, add linoleic acid and N, N'-dicyclohexyl diimide under stirring, heat to 110°C, reflux and stir for 48 hours, then centrifuge for 10 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain boron nitride containing alkenyl groups on the surface; the amount ratio of hydroxylated boron nitride, toluene, linoleic acid and N, N'-dicyclohexyl diimide is 5g:120mL:10g:2g;

[0046] Step A3: Add the alkenyl-containing boron nitride to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4 hours to obtain an epoxy product; the amount ratio of the alkenyl-containing boron nitride, dichloromethane and 3-chloroperoxybenzoic acid is 12g:80mL:0.1mol;

[0047] Step A4: Add 2-cyanophenothiazine to tetrahydrofuran, start stirring, add Raney nickel and Pd / C, introduce hydrogen, and react under normal pressure with stirring for 48 hours to obtain a primary amino product; add the primary amino product and the epoxy product to a flask, add dimethyl sulfoxide, react at 60°C with stirring for 24 hours, filter and dry to obtain a thermal conductive filler; the amount ratio of 2-cyanophenothiazine, tetrahydrofuran, Raney nickel and Pd / C is 0.1 mol:100 mL:0.02 mol:0.05 mol; the amount ratio of the primary amino product, the epoxy product and dimethyl sulfoxide is 46 g:14 g:150 mL.

[0048] Example 2

[0049] A thermally conductive filler, the preparation of which comprises the following steps:

[0050] Step A1: Mix potassium hydroxide and sodium hydroxide and grind them for 40 minutes, then place them in a high-pressure reactor, add hexagonal boron nitride, heat and react at 180°C for 2 hours, filter and centrifuge to obtain hydroxylated boron nitride; the amount ratio of potassium hydroxide, sodium hydroxide and hexagonal boron nitride is 48.5 mol:51.5 mol:13 g;

[0051] Step A2: Add hydroxylated boron nitride to toluene, ultrasonically disperse for 40 minutes, add linoleic acid and N, N'-dicyclohexyl diimide under stirring, heat to 115°C, reflux and stir for 50 hours, then centrifuge for 13 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain boron nitride containing alkenyl groups on the surface; the amount ratio of hydroxylated boron nitride, toluene, linoleic acid and N, N'-dicyclohexyl diimide is 6g:120mL:10g:2g;

[0052] Step A3: Add the alkenyl-containing boron nitride to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4.5 hours to obtain an epoxy product; the amount ratio of the alkenyl-containing boron nitride, dichloromethane and 3-chloroperoxybenzoic acid is 14g:85mL:0.1mol;

[0053] Step A4: Add 2-cyanophenothiazine to tetrahydrofuran, start stirring, add Raney nickel and Pd / C, introduce hydrogen, and react under normal pressure with stirring for 48 hours to obtain a primary amino product; add the primary amino product and the epoxy product to a flask, add dimethyl sulfoxide, stir and react at 60°C for 24 hours, filter and dry to obtain a thermal conductive filler; the amount ratio of 2-cyanophenothiazine, tetrahydrofuran, Raney nickel and Pd / C is 0.1 mol:105 mL:0.02 mol:0.05 mol; the amount ratio of the primary amino product, the epoxy product and dimethyl sulfoxide is 48 g:16 g:150 mL.

[0054] Example 3

[0055] A thermally conductive filler, the preparation of which comprises the following steps:

[0056] Step A1: Mix potassium hydroxide and sodium hydroxide and grind them for 45 minutes, then place them in a high-pressure reactor, add hexagonal boron nitride, heat and react at 180°C for 2 hours, and obtain hydroxylated boron nitride by filtering and centrifugation; the dosage ratio of potassium hydroxide, sodium hydroxide and hexagonal boron nitride is 48.5 mol:51.5 mol:15 g;

[0057] Step A2: Add hydroxylated boron nitride to toluene, ultrasonically disperse for 40 minutes, add linoleic acid and N, N'-dicyclohexyl diimide under stirring, heat to 120°C, reflux and stir for 51 hours, then centrifuge for 15 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain boron nitride containing alkenyl groups on the surface; the amount ratio of hydroxylated boron nitride, toluene, linoleic acid and N, N'-dicyclohexyl diimide is 7g:120mL:10g:2g;

[0058] Step A3: Add the alkenyl-containing boron nitride to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 5 hours to obtain an epoxy product; the amount ratio of the alkenyl-containing boron nitride, dichloromethane and 3-chloroperoxybenzoic acid is 16g:90mL:0.1mol;

[0059] Step A4: Add 2-cyanophenothiazine to tetrahydrofuran, start stirring, add Raney nickel and Pd / C, introduce hydrogen, and react under normal pressure with stirring for 48 hours to obtain a primary amino product; add the primary amino product and the epoxy product to a flask, add dimethyl sulfoxide, stir and react at 60°C for 24 hours, filter and dry to obtain a thermal conductive filler; the amount ratio of 2-cyanophenothiazine, tetrahydrofuran, Raney nickel and Pd / C is 0.1 mol:110 mL:0.02 mol:0.06 mol; the amount ratio of the primary amino product, the epoxy product and dimethyl sulfoxide is 50 g:18 g:150 mL.

[0060] Example 4

[0061] An anti-hydrolysis agent, the preparation of which comprises the following steps:

[0062] Step B1: Add 4-nitrostyrene to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, and stir at room temperature for 4 hours to obtain the epoxy product 1; the amount ratio of 4-nitrostyrene, dichloromethane and 3-chloroperbenzoic acid is 0.1 mol:50 mL:0.1 mol;

[0063] Step B2: In a nitrogen atmosphere, 1,3-bis(3-carboxypropyl)tetramethyldisiloxane and toluene were added to a flask, the temperature was raised to 45°C, pyridine was added, stirring was started, the epoxy product 1 was added to the flask, the reaction was stirred for 8 hours, and then the temperature was raised to 110°C and stirred for 1 hour to obtain a nitro product; the amount ratio of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane, toluene, pyridine and epoxy product 1 was 0.1 mol:180 mL:0.020 mol:0.2 mol;

[0064] Step B3: After mixing the nitro product and hexyl isocyanate, add a 20% by mass sulfuric acid solution and methanol, and react at 50°C for 4 hours to obtain a nitro product containing carbamate; add the nitro product containing carbamate and ethyl acetate into a three-necked flask, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1 hour to obtain a dibasic aromatic primary amine; the amount ratio of the nitro product, hexyl isocyanate, 20% by mass sulfuric acid solution and methanol is 1 mol: 2 mol: 100 mL: 200 mL; the amount ratio of the nitro product containing carbamate, ethyl acetate and sodium dithionite is 0.1 mol: 240 mL: 0.2 mol;

[0065] Step B4: Add xylene to a four-necked flask, introduce nitrogen, add dibasic aromatic primary amine and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain dibasic isocyanate; add dibasic isocyanate to a flask, then add 3-methyl-1-phenyl-2-phospholine-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; the amount ratio of xylene, dibasic aromatic primary amine and triphosgene is 260mL:0.1mol:0.2mol; the amount ratio of dibasic isocyanate and 3-methyl-1-phenyl-2-phospholine-1-oxide is 0.1mol:0.0030mol.

[0066] Example 5

[0067] An anti-hydrolysis agent, the preparation of which comprises the following steps:

[0068] Step B1: Add 4-nitrostyrene to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, and stir at room temperature for 4.5 hours to obtain the epoxy product 1; the amount ratio of 4-nitrostyrene, dichloromethane and 3-chloroperbenzoic acid is 0.1 mol:55 mL:0.1 mol;

[0069] Step B2: In a nitrogen atmosphere, 1,3-bis(3-carboxypropyl)tetramethyldisiloxane and toluene were added to a flask, the temperature was raised to 45°C, pyridine was added, stirring was started, the epoxy product 1 was added to the flask, the reaction was stirred for 9 hours, and then the temperature was raised to 115°C and stirred for 1.5 hours to obtain a nitro product; the amount ratio of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane, toluene, pyridine and epoxy product 1 was 0.1 mol:185 mL:0.023 mol:0.2 mol;

[0070] Step B3: After mixing the nitro product and hexyl isocyanate, add a 20% by mass solution of dilute sulfuric acid and methanol, and react at 50°C for 4 hours to obtain a nitro product containing carbamate; add the nitro product containing carbamate and ethyl acetate into a three-necked flask, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 1.3 hours to obtain a dibasic aromatic primary amine; the amount ratio of the nitro product, hexyl isocyanate, 20% by mass solution of dilute sulfuric acid and methanol is 1 mol: 2 mol: 100 mL: 200 mL; the amount ratio of the nitro product containing carbamate, ethyl acetate and sodium dithionite is 0.1 mol: 245 mL: 0.23 mol;

[0071] Step B4: Add xylene to a four-necked flask, introduce nitrogen, add dibasic aromatic primary amine and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain dibasic isocyanate; add dibasic isocyanate to a flask, then add 3-methyl-1-phenyl-2-phospholine-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; the amount ratio of xylene, dibasic aromatic primary amine and triphosgene is 260mL:0.1mol:0.2mol; the amount ratio of dibasic isocyanate and 3-methyl-1-phenyl-2-phospholine-1-oxide is 0.1mol:0.0033mol.

[0072] Example 6

[0073] An anti-hydrolysis agent, the preparation of which comprises the following steps:

[0074] Step B1: Add 4-nitrostyrene to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, and stir at room temperature for 5 hours to obtain the epoxy product 1; the amount ratio of 4-nitrostyrene, dichloromethane and 3-chloroperbenzoic acid is 0.1 mol:60 mL:0.1 mol;

[0075] Step B2: In a nitrogen atmosphere, 1,3-bis(3-carboxypropyl)tetramethyldisiloxane and toluene were added to a flask, the temperature was raised to 45°C, pyridine was added, stirring was started, the epoxy product 1 was added to the flask, the reaction was stirred for 10 hours, and then the temperature was raised to 120°C and stirred for 2 hours to obtain a nitro product; the amount ratio of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane, toluene, pyridine and epoxy product 1 was 0.1 mol:190 mL:0.025 mol:0.2 mol;

[0076] Step B3: After mixing the nitro product and hexyl isocyanate, add a 20% by mass solution of dilute sulfuric acid and methanol, and react at 50°C for 4 hours to obtain a nitro product containing carbamate; add the nitro product containing carbamate and ethyl acetate into a three-necked flask, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 1.5 hours to obtain a dibasic aromatic primary amine; the amount ratio of the nitro product, hexyl isocyanate, 20% by mass solution of dilute sulfuric acid and methanol is 1 mol: 2 mol: 100 mL: 200 mL; the amount ratio of the nitro product containing carbamate, ethyl acetate and sodium dithionite is 0.1 mol: 250 mL: 0.25 mol;

[0077] Step B4: Add xylene to a four-necked flask, introduce nitrogen, add dibasic aromatic primary amine and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain dibasic isocyanate; add dibasic isocyanate to a flask, then add 3-methyl-1-phenyl-2-phospholine-1-oxide, introduce nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent; the amount ratio of xylene, dibasic aromatic primary amine and triphosgene is 260mL:0.1mol:0.2mol; the amount ratio of dibasic isocyanate and 3-methyl-1-phenyl-2-phospholine-1-oxide is 0.1mol:0.0035mol.

[0078] Example 7

[0079] A scratch-resistant and wear-resistant overhead cable, comprising a conductor, an insulating layer and a sheath layer from the inside to the outside; the conductor is formed by twisting a plurality of hard copper wires, and the insulating layer is made of a cross-linked polyethylene insulating material;

[0080] The sheath layer comprises the following raw materials by weight: 60 parts of polyurethane resin, 15 parts of thermal conductive filler, 10 parts of flame retardant, 0.8 parts of ultraviolet absorber, and 1 part of anti-hydrolysis agent; the flame retardant is DOPO, and the ultraviolet absorber is UV-329;

[0081] The preparation of the scratch-resistant and wear-resistant overhead cable comprises the following steps:

[0082] Step S1: placing the polyurethane resin in a drying oven at 105° C. for 7 hours to obtain a dried polyurethane resin, placing the thermal conductive filler, flame retardant, ultraviolet absorber obtained in Example 1, and anti-hydrolysis agent obtained in Example 4 in an infrared dryer for 35 minutes, adding them together with the dried polyurethane resin to a mixer, stirring and mixing at a speed of 200 r / min for 10 minutes to obtain a mixture, and melt-extruding and granulating the mixture in a twin-screw extruder to obtain a sheath layer material;

[0083] Step S2: twist 14 hard copper wires to form a conductor; extrude a cross-linked polyethylene insulation material on the outer periphery of the conductor to form an insulation layer; and finally extrude the sheath layer material on the outer periphery of the insulation layer to form a sheath layer, thereby obtaining a scratch-resistant and wear-resistant overhead cable.

[0084] Example 8

[0085] A scratch-resistant and wear-resistant overhead cable, comprising a conductor, an insulating layer and a sheath layer from the inside to the outside; the conductor is formed by twisting a plurality of hard copper wires, and the insulating layer is made of a cross-linked polyethylene insulating material;

[0086] The sheath layer comprises the following raw materials by weight: 70 parts of polyurethane resin, 20 parts of thermal conductive filler, 13 parts of flame retardant, 0.9 parts of ultraviolet absorber, and 1.3 parts of anti-hydrolysis agent; the flame retardant is DOPO, and the ultraviolet absorber is UV-329;

[0087] The preparation of the scratch-resistant and wear-resistant overhead cable comprises the following steps:

[0088] Step S1: placing the polyurethane resin in a drying oven at 105° C. for 7.5 hours to obtain a dried polyurethane resin, placing the thermal conductive filler, flame retardant, ultraviolet absorber obtained in Example 2, and anti-hydrolysis agent obtained in Example 5 in an infrared dryer for 40 minutes, adding them together with the dried polyurethane resin to a mixer, stirring and mixing at a speed of 200 r / min for 13 minutes to obtain a mixture, and melt-extruding and granulating the mixture in a twin-screw extruder to obtain a sheath layer material;

[0089] Step S2: twist 16 hard copper wires to form a conductor; extrude a cross-linked polyethylene insulation material on the outer periphery of the conductor to form an insulation layer; and finally extrude the sheath layer material on the outer periphery of the insulation layer to form a sheath layer, thereby obtaining a scratch-resistant and wear-resistant overhead cable.

[0090] Example 9

[0091] A scratch-resistant and wear-resistant overhead cable, comprising a conductor, an insulating layer and a sheath layer from the inside to the outside; the conductor is formed by twisting a plurality of hard copper wires, and the insulating layer is made of a cross-linked polyethylene insulating material;

[0092] The sheath layer comprises the following raw materials by weight: 80 parts of polyurethane resin, 25 parts of thermal conductive filler, 15 parts of flame retardant, 1.0 parts of ultraviolet absorber, and 1.5 parts of anti-hydrolysis agent; the flame retardant is DOPO, and the ultraviolet absorber is UV-329;

[0093] The preparation of the scratch-resistant and wear-resistant overhead cable comprises the following steps:

[0094] Step S1: placing the polyurethane resin in a drying oven at 105° C. for 8 hours to obtain a dried polyurethane resin, placing the thermal conductive filler, flame retardant, ultraviolet absorber obtained in Example 3, and anti-hydrolysis agent obtained in Example 6 in an infrared dryer for 45 minutes, adding them together with the dried polyurethane resin to a mixer, stirring and mixing at a speed of 300 r / min for 15 minutes to obtain a mixture, and melt-extruding and granulating the mixture in a twin-screw extruder to obtain a sheath layer material;

[0095] Step S2: twist 18 hard copper wires to form a conductor; extrude a cross-linked polyethylene insulation material on the outer periphery of the conductor to form an insulation layer; and finally extrude the sheath layer material on the outer periphery of the insulation layer to form a sheath layer, thereby obtaining a scratch-resistant and wear-resistant overhead cable.

[0096] Comparative Example 1

[0097] This comparative example is a commercially available overhead cable with a polyurethane material as the sheath layer material.

[0098] Comparative Example 2

[0099] Compared with Example 9, the thermally conductive filler is replaced with the epoxy product in Example 3, that is, the phenothiazine structure is not introduced, and the rest is exactly the same as Example 9 to produce a scratch-resistant and wear-resistant overhead cable.

[0100] Comparative Example 3

[0101] Compared with Example 9, the 1,3-bis(3-carboxypropyl)tetramethyldisiloxane used in Example 6 is replaced with pimelic acid, i.e., no polysiloxane chain is introduced, and the anti-hydrolysis agent a prepared according to the reaction steps of Example 6 replaces the anti-hydrolysis agent prepared in the original Example 6 to prepare a scratch-resistant and wear-resistant overhead cable.

[0102] The scratch-resistant and wear-resistant overhead cable prepared by the present invention is further tested for its effects, and the test results are as follows.

[0103] In order to test the scratch-resistant and wear-resistant overhead cable of the present invention, the sheath layer materials for the overhead cables obtained in Examples 7-9 and Comparative Examples 1-3 were subjected to tensile strength and elongation at break tests according to GB / T2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Electric Cables and Optical Cables"; the sheath layer materials were placed in an air box and aged at 80°C for 168h, and the tensile strength and elongation at break retention rates were tested according to the method of GB / T2951-2008; the thermal conductivity of the sheath layer material was tested using a transient thermal conductivity meter, and the sample specifications were 100×5×5mm 3, each sample was tested 5 times and the average value was taken; the sheath layer material was placed at 60°C for hydrolysis for 48 hours, and the tensile strength change rate was measured according to the GB / T2951-2008 method; the sample was prepared according to GB / T9352-2008 and the Vicat softening temperature was tested using the A50 method; the results are recorded in Table 1;

[0104] Table 1:

[0105]

[0106] According to the data in Table 1, it can be seen from the comparison of Example 7, Example 8 and Example 9 with Comparative Example 1 that the scratch-resistant and wear-resistant overhead cable of the present invention has good heat dissipation, mechanical properties, aging resistance, hydrolysis resistance and heat resistance. It can be seen from the comparison of Example 9 with Comparative Example 2 that the use of thermal conductive fillers and the introduction of phenothiazine structures improve the aging resistance of the prepared cable. It can be seen from the comparison of Example 9 with Comparative Example 3 that the use of anti-hydrolysis agents and the introduction of polysiloxane chains make the anti-hydrolysis agents have excellent hydrolysis resistance and good heat resistance.

[0107] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A scratch-resistant and wear-resistant overhead cable, characterized in that: From the inside to the outside, it includes a conductor, an insulating layer and a sheath layer; the sheath layer includes the following raw materials by weight: 60-80 parts of polyurethane resin, 15-25 parts of thermal conductive filler, 10-15 parts of flame retardant, 0.8-1.0 parts of ultraviolet absorber, and 1-1.5 parts of anti-hydrolysis agent; The preparation of the thermally conductive filler comprises the following steps: Step A1: Mix potassium hydroxide and sodium hydroxide and grind them for 35-45 minutes, then place them in a high-pressure reactor, add hexagonal boron nitride, heat and react at 180° C. for 2 hours, and obtain hydroxylated boron nitride by filtering and centrifuging; Step A2: Add hydroxylated boron nitride to toluene, ultrasonically disperse for 40 minutes, add linoleic acid and N, N'-dicyclohexyl diimide under stirring, heat to 110-120°C, reflux with constant temperature stirring for 48-51 hours, then centrifuge for 10-15 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain boron nitride containing alkenyl groups on the surface; Step A3: Add the boron nitride containing alkenyl groups on the surface into dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, and stir at room temperature for 4-5 hours to obtain an epoxy product; Step A4: Add 2-cyanophenothiazine to tetrahydrofuran, start stirring, add Raney nickel and Pd / C, introduce hydrogen, and stir to react for 48 hours at normal pressure to obtain a primary amino product; add the primary amino product and the epoxy product to a flask, add dimethyl sulfoxide, stir to react at 60°C for 24 hours, filter and dry to obtain a thermally conductive filler.

2. The scratch-resistant and wear-resistant overhead cable according to claim 1, characterized in that: In step A1, the usage ratio of potassium hydroxide, sodium hydroxide and hexagonal boron nitride is 48.5 mol:51.5 mol:10-15 g; in step A2, the usage ratio of hydroxylated boron nitride, toluene, linoleic acid and N,N'-dicyclohexyldiimide is 5-7 g:120 mL:10 g:2 g.

3. The scratch-resistant and wear-resistant overhead cable according to claim 1, characterized in that: In step A3, the amount ratio of the boron nitride containing alkenyl groups on the surface, dichloromethane and 3-chloroperoxybenzoic acid is 12-16 g: 80-90 mL: 0.1 mol.

4. The scratch-resistant and wear-resistant overhead cable according to claim 1, characterized in that: In step A4, the usage ratio of 2-cyanophenothiazine, tetrahydrofuran, Raney nickel and Pd / C is 0.1 mol: 100-110 mL: 0.02 mol: 0.05-0.06 mol; the usage ratio of primary amino product, epoxy product and dimethyl sulfoxide is 46-50 g: 14-18 g: 150 mL.

5. The scratch-resistant and wear-resistant overhead cable according to claim 1, characterized in that: The preparation of the anti-hydrolysis agent comprises the following steps: Step B1: Add 4-nitrostyrene to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, and stir at room temperature for 4-5 hours to obtain the epoxy product 1; Step B2: In a nitrogen atmosphere, add 1,3-bis(3-carboxypropyl)tetramethyldisiloxane and toluene into a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product 1 into the flask, stir and react for 8-10h, then heat to 110-120°C, stir for 1-2h to obtain the nitro product; Step B3: After mixing the nitro product and hexyl isocyanate, add a 20% by mass dilute sulfuric acid solution and methanol, and react at 50° C. for 4 hours to obtain a nitro product containing carbamate; add the nitro product containing carbamate and ethyl acetate into a three-necked flask, heat to 45-55° C., start reflux stirring, then add sodium dithionite, and reflux stirring for 1-1.5 hours to obtain a dibasic aromatic primary amine; Step B4: Add xylene to a four-necked flask, pass nitrogen, add dibasic aromatic primary amine and triphosgene at 75°C respectively, and after the addition is completed, heat to 125°C and continue to react for 3.5 hours to obtain dibasic isocyanate; add dibasic isocyanate to the flask, then add 3-methyl-1-phenyl-2-phosphopentene-1-oxide, pass nitrogen, heat to 165°C with stirring, and react at a constant temperature for 12 hours to obtain an anti-hydrolysis agent.

6. The scratch-resistant and wear-resistant overhead cable according to claim 5, characterized in that: In step B1, the amount ratio of 4-nitrostyrene, dichloromethane and 3-chloroperbenzoic acid is 0.1 mol: 50-60 mL: 0.1 mol; in step B2, the amount ratio of 1,3-bis(3-carboxypropyl)tetramethyldisiloxane, toluene, pyridine and epoxy product 1 is 0.1 mol: 180-190 mL: 0.020-0.025 mol: 0.2 mol.

7. The scratch-resistant and wear-resistant overhead cable according to claim 5, characterized in that: In step B3, the amount ratio of the nitro product, hexyl isocyanate, 20% dilute sulfuric acid solution and methanol is 1 mol: 2 mol: 100 mL: 200 mL; the amount ratio of the nitro product containing carbamate, ethyl acetate and sodium dithionite is 0.1 mol: 240-250 mL: 0.2-0.25 mol.

8. The scratch-resistant and wear-resistant overhead cable according to claim 5, characterized in that: In step B4, the usage ratio of xylene, dibasic aromatic primary amine and triphosgene is 260mL:0.1mol:0.2mol; the usage ratio of dibasic isocyanate and 3-methyl-1-phenyl-2-phosphopentene-1-oxide is 0.1mol:0.0030-0.0035mol.

9. The scratch-resistant and wear-resistant overhead cable according to claim 1, characterized in that: The conductor is formed by twisting a number of hard copper wires, and the insulating layer is made of cross-linked polyethylene insulating material; the flame retardant is DOPO, and the ultraviolet absorber is UV-329.

10. The production process of a scratch-resistant and wear-resistant overhead cable according to claim 1, characterized in that: The steps include: Step S1: placing the polyurethane resin in a drying oven at 105° C. for 7-8 hours to obtain a dried polyurethane resin, placing the thermal conductive filler, flame retardant, ultraviolet absorber, and anti-hydrolysis agent in an infrared dryer for 35-45 minutes, adding them together with the dried polyurethane resin to a mixer, stirring and mixing at a speed of 200-300 r / min for 10-15 minutes to obtain a mixture, and melt-extruding and granulating the mixture in a twin-screw extruder to obtain a sheath layer material; Step S2: twisting a number of hard copper wires to form a conductor; extruding a cross-linked polyethylene insulation material on the outer periphery of the conductor to form an insulation layer; and finally extruding the sheath layer material on the outer periphery of the insulation layer to form a sheath layer, thereby obtaining a scratch-resistant and wear-resistant overhead cable.

Citation Information

Cited By

  • High-thermal-conductivity interface material composition and preparation method thereof

    CN120025687A